Regulator insight on the establishment of socialbased healthcare institutions in Malaysia - Yasin, Nurul Ibtisyami; Atan, Nur Atika; Samad, Rose Ruziana; Mohd Fadzil, Mohd Idris; Kefeli, Zurina; Johari, Fuadah (Malque Publishing, 2025)
Social innovation is gaining significant recognition in research and policy domains, including within the healthcare sector. Institutions based on trade and business principles have accumulated social capital to pursue social objectives. However, the sustainability of these social-based healthcare institutions remains uncertain. Regulatory insights are essential for the development and maintenance of these institutions in the future. This qualitative study aims to explore and understand the perspective of the Division of Medical Practice and Private Services (CKAPS) on the establishment and sustainability of social-based healthcare institutions. Consequently, primary data were collected through interviews with officers at the CKPAS, while secondary data were obtained from documentary analysis of Act 586 and related documents. The transcripts were analyzed inductively using NVivo software, with codes and themes developed based on a preestablished conceptual framework. The findings reveal no definitional distinction between social-based and profit-based private healthcare providers. Both types of institutions are governed by Act 586 and its subsidiary regulations regarding establishment, maintenance, and licensing. Practically, social-based healthcare can be identified through 1) self-declaration, 2) documents such as tax exemption letter from LHDN or the National Audit Department, and 3) information from the public. To ensure sustainability, social-based healthcare institutions must adhere to the principles outlined in Act 586, which emphasize comprehensive planning and robust proposals. Healthcare quality is the top priority and should not be forgotten to reduce the cost of healthcare in an attempt to serve the poor. Thus, these institutions need to be financially, socially, and environmentally sustainable, managed by qualified and experienced leadership teams. The key critical contribution of this study is that it presents new evidence regarding the impacts of government policies towards the establishment and sustainability of social-based healthcare institutions.